Dried Mixed Culture of Lactobacillus sp and Saccharomyces cereviceae Production - Putri, Widya Dwi Rukmi; Widyaningsih, Dewanti; Ningtyas, D. W (Jurnal Teknologi Pertanian, 2008)
Recently, fermentation process of cereal and legume–based products has been developed. In the fermentation process, the aviability of starter cultures is needed. Starter cultures that usually used to ferment cereal are Lactobacillus and yeasts. Generally, the starter cultures are used in liquid form and it needs to be periodically regenerated, that will lead to strain degeneration. To overcome the problem and to make the starter cultures easy to use, it can be made in dried form.  In this research, we studied to increase biomass cells of dried cultures that affected by some factors. The aims of this research were to evaluate the suitable medium, growing methods, substrate:culture ratio, and incubation time to get the highest  biomass cells of dried starter cultures. Starter culture in corn medium and the mixed culture method had the highest capability for growing. Whereas, substrate to culture ratio (94:6) and incubation time of 24 hours showed the best viability of these microorganism, and the best dried starter cultures with total BAL of 2.2X109 cfu/ml and total yeast of 3.0X108  cfu/ml. The best result on this treatment was stored at room and refrigeration temperatures for 4 weeks and the best stored proved on refrigeration which is can maintened viability of dried cultures.Keywords: mixed culture, vacuum drying, dried culture